Territorial aspects and temporality on the distribution of monuments of Campo Grande, Mato Grosso do Sul - Batiston, Fernando Cesar Pires; Coutinho, Dolores Pereira Ribeiro; Borges, Pedro Pereira (Revista Nacional de Gerenciamento de Cidades, 2023)
This study’s objective is to analyze cultural, material and immovable goods that are a part of the Cultural Heritage of Campo Grande, Mato Grosso do Sul, Brazil. In order to do that, a document and bibliographical review about the city’s cultural heritage was made. This study refers to monuments that, aside from being cultural, material and immovable goods, bearers of their particular immateriality, are characterized by their functions of guiding the community in the urban fabric, enhancing the city landscape, concentrating symbolic elements, and disseminating memory, which stimulate inhabitants and dwellers of a certain place in a way or another. Considering the stated content, it was possible to identify the existence of an irregular distribution of the 66 monuments in Campo Grande’s territorial space and, in what pertains to creation of new monuments, to observe that, over time, their production can be divided into six distinct periods, by taking under consideration factors of production, historical context and themes addressed.